Effects of a long-term vitamin D and calcium supplementation on falls and parameters of muscle function in community-dwelling older individuals - Pfeifer, M.; Begerow, B.; Minne, H. W.; Suppan, K.; Fahrleitner-Pammer, A.; Dobnig, H. (Osteoporosis international, 2009)
Summary In 242 community-dwelling seniors, supplementation with either 1000 mg of calcium or 1000 mg of calcium plus vitamin D resulted in a decrease in the number of subjects with first falls of 27% at month 12 and 39% at month 20. Additionally, parameters of muscle function improved significantly. Introduction The efficacy of vitamin D and calcium supplementation on risk of falling in the elderly is discussed controversially. Randomized controlled trials using falls as primary outcome are needed. We investigated long-term effects of calcium and vitamin D on falls and parameters of muscle function in community-dwelling elderly women and men. Methods Our study population consisted of 242 individuals recruited by advertisements and mailing lists (mean [ ± SD] age, 77 ± 4 years). All serum 25-hydroxyvitamin D (25[OH]D) levels were below 78 nmol/l. Individuals received in a double blinded fashion either 1000 mg of calcium or 1000 mg of calcium plus 800 IU of vitamin D per day over a treatment period of 12 months, which was followed by a treatment-free but still blinded observation period of 8 months. Falls were documented using diaries. The study took place in Bad Pyrmont, Germany (latitude 52°) and Graz, Austria (latitude 46°). Results Compared to calcium mono, supplementation with calcium plus vitamin D resulted in a significant decrease in the number of subjects with first falls of 27% at month 12 (RR = 0.73; CI = 0.54–0.96) and 39% at month 20 (RR = 0.61; CI = 0.34–0.76). Concerning secondary endpoints, we observed significant improvements in quadriceps strength of 8%, a decrease in body sway of 28%, and a decrease in time needed to perform the TUG test of 11%. Discussion Combined calcium and vitamin D supplementation proved superior to calcium alone in reducing the number of falls and improving muscle function in community-dwelling older individuals.